Loyalty Card Membership Challenge: A Study on Membership Churn and their Spending Behaviour - Lim, Tong Ming *; Lee, Angela Siew Hoong *; Chia, Mark P. C; Soam, Wei Jie; Liew, Kasper Yuet Hon (Society for Science and Education, 2017)
Understand member spending behaviour and their loyalty is important in all industries. By gaining loyalty from customers and understand how they spend, companies are able to retain their customers, increase their revenue and plan their marketing strategy to continue grow their business in a competitive business ecosystem. This research investigates member spending behaviour and membership churn for a loyalty card company in Malaysia. This research conducts exploratory analysis on three key partners registered with the company to understand their outlets’ spending activities and patterns. Meanwhile, this research also model membership churn based on the last 24 months membership data to identify factors that influence membership churn so that effective strategy can be formulated to retain active members in the company.